Composite fuel based on residue from tyre and secondary polymer pyrolysis - Popov V.; Papin A.; Ignatova A.; Makarovskikh A. V. Aleksandra Viktorovna (Latest Research in Hydrocarbon Refining, 2016)
Title screen